SPACE FOR REALIZING STRATEGIES OF STUDENTS' PERSONAL AND PROFESSIONAL DEVELOPMENT - Igor A. Loginov; Anatoly Yu. Belogurov; Maya A. Kulygina (Высшее образование в России)
The article describes the experience of MGIMO-University in organizing educational activities with a stress on axiological aspect. The authors analyze the trends in developing civic and social competences of students in the process of getting involved in various scientific, education and social projects.